2012
DOI: 10.1185/03007995.2012.681637
|View full text |Cite
|
Sign up to set email alerts
|

Annualized relapse rate of first-line treatments for multiple sclerosis: a meta-analysis, including indirect comparisons versus fingolimod

Abstract: Our study demonstrated that fingolimod significantly reduces relapse frequency in patients with RRMS compared with current first-line disease-modifying therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
26
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 36 publications
3
26
0
Order By: Relevance
“…In our analysis, we have used treatment and study as classification variables putting a random effect on treatment. The distribution is conditional on random treatment effect [7][8][9] and is in line with Lu and Ades 10 . A comprehensive description of model and statements was out of scope of the publication.…”
Section: Efficacy Sectionsupporting
confidence: 59%
See 1 more Smart Citation
“…In our analysis, we have used treatment and study as classification variables putting a random effect on treatment. The distribution is conditional on random treatment effect [7][8][9] and is in line with Lu and Ades 10 . A comprehensive description of model and statements was out of scope of the publication.…”
Section: Efficacy Sectionsupporting
confidence: 59%
“…Since PROC GLIMMIX is a well established and widely used method under generalized linear models 7,8 , the explanation provided in the manuscript can be considered appropriate and sufficient within the scope of the research question. However, we can answer specific questions around the model on requests.…”
Section: Efficacy Sectionmentioning
confidence: 99%
“…These compare favourably, to within a 10% range, which is adequate for approximate comparisons. More formal attempts to compare trials using network meta-analysis and similar approaches have shown conflicting results [65][66][67][68]. What is striking in the comparison shown in Table 1 is the high degree of concordance between the observed effect on Gad-enhancing lesions and relapse rates and between measures of brain atrophy and disability progression in what is a very consistent pattern across therapies.…”
Section: Comparative Efficacymentioning
confidence: 73%
“…Roskell et al performed an indirect comparison of ARR using mixed treatment comparison framework for fingolimod versus GA, IFN β-1b and IFN β-1a [39]. Fingolimod significantly reduced relapse frequency compared with injectable first-line DMTs.…”
Section: Discussionmentioning
confidence: 99%